TINJAUAN TERHADAP RENCANA PENERAPAN PAJAK LINGKUNGAN SEBAGAI INSTRUMEN PERLINDUNGAN LINGKUNGAN HIDUP DI INDONESIA - Dahliana Hasan; Dinarjati Eka Puspitasari (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
Research on “an analysis on Indonesia’s Environmental Tax Planning as an instrument of Environmental Preservation” is a normative research which has objectives to know the concept of environmental tax which is offered by Indonesian Government and to obtain a clear description whether it is a better concept or not which can be used to decrease environmental degradation. Data in this research were obtained through field research and library research. The field research was carried out by using interview guidance, whereas the library research was done by documentary study by way of collecting and analyzing selected laws and regulations, books, articles and other documents which were relevant to the research. All data were analyzed qualitatively. The result showed that the objective of the concept of environmental tax, offered by Indonesian government, is to decrease environmental degradation as a result of production process. Basically, the concept is a better instrument to preserve the environment, however, it should be reviewed especially on determining the taxpayer’s criteria, the tax rate and the budget earmarking in order to be applicable and to have no burden toward the industry itself. Now, it will be wise to rely on other policies to handle the environmental problems in Indonesia such as CSR, performance bonds, AMDAL and UKL-UPL, even though some weaknesses have also found on those policies.